Comparative Analysis of Toll Plaza Safety Features in Puerto Rico and Massachusetts with a Driving Simulator. Issue 1 (2017) - Valdés, Didier; Colucci, Benjamín; Knodler, Michael; Fisher, Donald; Ruiz, Bryan; Ruiz, Johnathan; García, Ricardo; Colón, Enid; Hajiseyedjavadi, Foroogh
Driving simulators have been widely used in transportation research and have potential applications for toll plaza safety research. The University of Puerto Rico at Mayagüez (UPRM) and the University of Massachusetts, Amherst (UMass-Amherst) performed a collaborative investigation using driving simulators to evaluate drivers' behavior in two toll plazas with different signage and lane configurations that operate under the U.S. jurisdiction. The studied toll roads were the Caguas South Toll Plaza in Puerto Rico and the West Springfield Toll Plaza in Massachusetts. The major safety issues identified in both toll roads were unexpected lane changes, sudden vehicle stops, and variable speed patterns. The purpose of this study was to exchange research scenarios between UPRM and UMass-Amherst to test drivers who were unfamiliar with the areas of the study and enlarge the scope. Assuming that the patterns of behavior were similar, the results would suggest that drivers' behaviors from different regions depend largely on the geometry of the toll plaza and not on the driving culture particular to a region. This study will greatly add to the utility of driving simulator studies because the results reported from one region and one toll plaza arrangement should generalize to other regions around the country and to territories. Results show that familiar drivers had a better driving performance, with respect to variability of lane position, when compared with unfamiliar drivers. However, the proposed treatments for each toll plaza improved road safety for both familiar and unfamiliar drivers.